Pengaruh Konten Youtube Binaragawan Ade Rai Terhadap Meleknya Hidup Sehat Di Gym D’max Kota Padang - Aldida, M. Bertu; ., Defhany (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
YouTube is a form of social media that is included in the New Media category. Healthy lifestyle behavior popularized by Ade Rai through content on YouTube is able to change the audience's perception of a healthy lifestyle. An initial survey conducted by researchers at Gym D'max Padang City found that respondents took a healthy lifestyle lightly, and thought that they only needed to consume healthy food without having to get enough rest. However, after watching the content created by Ade Rai, it provides important education regarding implementing a healthy lifestyle. Ade Rai always provides information from sources such as books, scientific journals and other trusted sources. Therefore, respondents to every content he uploads can have information that is educational and based on facts, so that the information he shares is useful. This research uses a quantitative type of research. The sampling technique is a simple random sampling technique with 55 permanent members of the Padang City D'Max Gym. Simple linear regression analysis was used to test the hypothesis with the SPSS 24 program. The results indicated that there was an influence of Bodybuilder Ade Rai's YouTube content on awareness of healthy living at the D'Max Gym, Padang City.